2013
DOI: 10.1371/journal.pone.0077982
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding the Canadian Arctic Flora: Core Plastid Barcodes (rbcL + matK) for 490 Vascular Plant Species

Abstract: Accurate identification of Arctic plant species is critical for understanding potential climate-induced changes in their diversity and distributions. To facilitate rapid identification we generated DNA barcodes for the core plastid barcode loci (rbcL and matK) for 490 vascular plant species, representing nearly half of the Canadian Arctic flora and 93% of the flora of the Canadian Arctic Archipelago. Sequence recovery was higher for rbcL than matK (93% and 81%), and rbcL was easier to recover than matK from he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 266 publications
(401 reference statements)
3
75
0
Order By: Relevance
“…A desirable DNA barcode should contain sufficient sequence variation to permit species discrimination and show significant inter-species differences with minimal intra-species variation, together with convenient flanking regions for PCR amplification and sequencing (CBOL Plant Working Group, 2009;Guo et al, 2011). The CBOL proposed using a combination of matK and rbcL as a plant barcode due to the above-mentioned features (Saarela et al, 2013). The two universal DNA barcodes used in this study, matK and rbcL, were successfully amplified by the universal primer and were found to exhibit interspecies specific variations that could be used to identify each species with little intra-species sequence divergence (Figures S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A desirable DNA barcode should contain sufficient sequence variation to permit species discrimination and show significant inter-species differences with minimal intra-species variation, together with convenient flanking regions for PCR amplification and sequencing (CBOL Plant Working Group, 2009;Guo et al, 2011). The CBOL proposed using a combination of matK and rbcL as a plant barcode due to the above-mentioned features (Saarela et al, 2013). The two universal DNA barcodes used in this study, matK and rbcL, were successfully amplified by the universal primer and were found to exhibit interspecies specific variations that could be used to identify each species with little intra-species sequence divergence (Figures S1 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Among the diverse DNA barcode candidates, maturase K (matK) and ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit (rbcL) are universal plant DNA barcodes that are used by the Consortium for the Barcode of Life (CBOL, 2009). These candidates are widely used as genetic markers to identify plant species and to analyze phylogenetic relationships (Kato et al, 1998;Kress and Erickson, 2007;Saarela et al, 2013). Chloroplast matK and rbcL DNA barcode regions have been used to identify species of diverse plant taxa, including herbal materials, and to clarify taxonomic origins (Cabrera et al, 2008;Sucher and Carles, 2008;Guo et al, 2011;Chao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For vascular plants, resolution was lower, with 54% of species forming monophyletic clusters based on barcode regions rbcLa and ITS2. This lack of resolution at the level of plant species is partly reflective of arctic genera encompassing relatively young and (or) little-diverged taxa (Kuzmina et al 2012;Saarela et al 2013). At the level of genera, resolution proves better, with 78% of the genera assessed forming monophyletic clades for the two gene regions combined.…”
Section: Barcoding An Arctic Food Webmentioning
confidence: 99%
“…Dwarf plants with a heavily marcescent habit, Festuca edlundiae, were first differentiated from the phenotypically variable Festuca hyperborea Holmen ex Frederiksen (High Arctic Fescue) based on isozymes (Aiken et al 1995). Hybridization and introgression between Festuca edlundiae and the other high Arctic Festuca species have been documented (Saarela et al 2013), but taxonomic boundaries between the various species are well understood and various keys exist separating the species using consistent morphologic characters (Fjellheim et al 2001;Guldahl et al 2001). using these keys, it may yet be found that Festuca edlundiae has been collected on Somerset Island before its recognition as a distinct taxon; nonetheless Sokoloff 128 is the first known report of this grass species on the island.…”
Section: Discussionmentioning
confidence: 99%